Path Analysis of Pearl Millet Yield and Yield Components under Moisture Stress - Yadav, O P; Mathur, B K; Manga, V K (Annals of Arid Zone, 2016)
Grain yield of pearl millet (Petmiserurn glaucurn) is influenced by several yield components. Path coefficient analysis was conducted to study the relationship between grain yield and its components. Thirty hybrids of pearl millet were grown under natural terminal moisture stress at Jodhpur. Grain yield mainly depended upon threshing percentage, biological yield and number of panicles m-2. Early maturing genotypes yielded higher. Longer duration of pre-flowering period affected inversely seed weight and threshing percentage. Seed weight showed negligible direct effect on grain yield but influenced it through threshing percentage. Similarly plan: height influenced grain yield via biological yield.